GlyT1 encephalopathy: Characterization of presumably disease causing GlyT1 mutations. (October 2020) - Hauf, K.; Barsch, L.; Bauer, D.; Buchert, R.; Armbruster, A.; Frauenfeld, L.; Grasshoff, U.; Eulenburg, V.
Abstract: Glycine constitutes a major inhibitory neurotransmitter predominantly in caudal regions of the CNS. The extracellular glycine concentration is regulated synergistically by two high affinity, large capacity transporters GlyT1 and GlyT2. Both proteins are encoded by single genes SLC6A9 and SLC6A5, respectively. Mutations within the SLC6A5 gene encoding for GlyT2 have been demonstrated to be causative for hyperekplexia (OMIM #614618), a complex neuromuscular disease, in humans. In contrast, mutations within the SLC6A9 gene encoding for GlyT1 have been associated with GlyT1 encephalopathy (OMIM #601019), a disease causing severe postnatal respiratory deficiency, muscular hypotonia and arthrogryposis. The consequences of the respective GlyT1 mutations on the function of the transporter protein, however, have not yet been analysed. In this study we present the functional characterisation of three previously published GlyT1 mutations, two mutations predicted to cause truncation of GlyT1 (GlyT1 Q573 * and GlyT1 K310F+fs * 31 ) and one predicted to cause an amino acid exchange within transmembrane domain 7 of the transporter (GlyT1 S407G ), that are associated with GlyT1 encephalopathy. Additionally, the characterization of a novel mutation predicted to cause an amino acid exchange within transmembrane domain 1 (GlyT1 V118M ) identified in two fetuses showing increased nuchal translucency and arthrogryposis in routine ultrasound scans is demonstrated. We show that in recombinant systems the two presumably truncating mutations resulted in an intracellular retained GlyT1 protein lacking the intracellular C-terminal domain. In both cases this truncated protein did not show any residual transport activity. The point mutations, hGlyT1 S407G and hGlyT1 V118M, were processed correctly, but showed severely diminished activity, thus constituting a functional knock-out in - vivo . Taken together our data demonstrate that all analysed mutations of GlyT1 that have been identified in GlyT1 encephalopathy patients cause severe impairment of transporter function. This is consistent with the idea that loss of GlyT1 function is indeed causal for the disease phenotype. Highlights: SLC6A9 (Glycine transporter 1) is a disease gene for human GlyT1 encephalopathy. Currently known GlyT1 mutations found in GlyT1 encephalopathy patients result in severe impairment of transporter function. Truncated transporters are retained intracellularly within the endoplasmatic reticulum. hGlyT1 S407G and hGlyT1 V118M are normally processed, but display dramatically reduced apparent glycine affinity.